Cell subpopulations dispersed from solid tumours and separated by centrifugal elutriation. - Siemann, D. W. (Nature Publishing Group, 1981)
The degree of non-neoplastic host-cell infiltration was assessed in 3 in vivo-in vitro tumour models commonly used in radiobiological studies: EMT6/Ro mammary carcinoma, 9L/Ro tumour and KHT sarcoma. While the 2 former tumour models have been shown to be moderately to highly immunogenic when grown s.c., the KHT sarcoma is apparently non-immunogenic. Using differential staining on single-cell suspensions from enzymatically dissociated solid tumours, all 3 tumour types were found to contain large proportions (30-60%) of non-neoplastic host cells. The actual host-cell component found in the cell suspensions differed both in type and percentage for the 3 tumours studied. These host and neoplastic cells in the cell suspensions prepared from the solid tumours could be readily separated by centrifugal elutriation. After separation the clonogenic potential of the neoplastic cells was assessed, and was found to be higher than the clonogenic capacity of the unseparated cell suspension by a factor directly related to the host/neoplastic cell ratio. Even after the removal of the host cells, the clonogenic capacities of the neoplastic EMT6 and 9L tumour cells were lower than that of the corresponding in vitro sublines (approximately 30 vs 75%). However, in the KHT sarcoma the removal of the host cell component raised the plating efficiency to approximately 60%, which was similar to the value for the in vitro cell subline of this tumour.